Direct use of waste vegetable oil in internal combustion engines. (March 2017) - Capuano, D.; Costa, M.; Di Fraia, S.; Massarotti, N.; Vanoli, L.
Abstract: Direct use of Waste Vegetable Oil (WVO) as fuel is very attractive to reduce fossil fuels utilization and increase sustainability. WVO incorrect disposal causes serious damages to sewage systems and wastewater treatment plants. Moreover, if WVO reaches natural ecosystems, such as rivers, aquifers or subsoil, the environmental consequences can be severe. In recent years, the main reuse of WVO has been in biodiesel production, which is remunerative under current tax allowance policies. However, biodiesel production requires complex physical–chemical treatments, while direct use of WVO just needs mechanical treatment. As a consequence, WVO direct use in energy conversion systems lower the impact, from the economic, energetic and environmental points of view, with respect to biodiesel production. Moreover, as concerns the environmental impact, it should be considered that the direct use of WVO as fuel produces less polluting emissions when considering the whole life cycle: carbon dioxide produced during combustion, in fact, can be partially absorbed by crops used for oil production. This paper presents a comprehensive review of the work done to evaluate the effects of direct use of WVO in internal combustion engines. Many authors have shown the advantages of using straight vegetable oils or biodiesel produced from WVO as fuel, while the benefits of WVO direct use have not yet been clearly presented. The available literature still presents few papers about this topic, therefore also the use of vegetable oil, that presents physical chemical characteristics very similar to those of WVO, has been taken into account. After a brief introduction, the characteristics of WVO most affecting its use as fuel have been studied. Then several applications of WVO direct use in internal combustion engines and the available fuel supply technologies have been considered. Finally, the energetic performance and the pollutant emissions reported in literature have been deeply analyzed.